2010
DOI: 10.1111/j.1365-2672.2010.04840.x
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of resistant gene markers for predicting treatment outcome on second-line anti-tuberculosis drugs

Abstract: Aim:  Mutations in rrs [nucleotide (nt) 1401], gyrA gene (codons 90, 91 or 94), tlyA, ethA and thyA genes of Mycobacterium tuberculosis (MTB) were evaluated for their usefulness in predicting treatment outcome of kanamycin (KM), capreomycin (CPM), ofloxacin (OFX), ethionamide (ETH) and para‐aminosalicylic acid (PAS). Methods and Results:  DNA sequence analyses of these genes were performed against 188 MTB isolates obtained from patients put on second‐line anti‐TB drugs (SLDs) with well‐documented clinical hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 27 publications
(53 reference statements)
0
31
1
Order By: Relevance
“…One study in 2001 reported that streptomycin resistance was related to mutations in the 500 region of rrs [22]. Our study followed primer patterns from one related study in Hong Kong that could predict 96.8% specificity and 64.2% sensitivity for kanamycin from rrs on gene marker 1401 [11]. showed 78% of kanamycin resistance correlated to SNPs in rrs at nt1401 [28] and concluded that the commercial diagnostic tool determining the aminoglycoside drug resistance target at rrs nt 1401 could detect 78% of kanamycin resistance in XDR-TB isolates [28].…”
Section: Kanamycin Resistancementioning
confidence: 99%
See 3 more Smart Citations
“…One study in 2001 reported that streptomycin resistance was related to mutations in the 500 region of rrs [22]. Our study followed primer patterns from one related study in Hong Kong that could predict 96.8% specificity and 64.2% sensitivity for kanamycin from rrs on gene marker 1401 [11]. showed 78% of kanamycin resistance correlated to SNPs in rrs at nt1401 [28] and concluded that the commercial diagnostic tool determining the aminoglycoside drug resistance target at rrs nt 1401 could detect 78% of kanamycin resistance in XDR-TB isolates [28].…”
Section: Kanamycin Resistancementioning
confidence: 99%
“…PCR product comprised 665 base pair fragments, according to the following steps: beginning denaturation at 95˚C for 2 min, followed by 35 cycles of 94˚C for 1 min, 60˚C for 1min, 68˚C for 2 min, followed by elongation at 68˚C for 10 min [11]. The amplified products were purified with a multiscreen filter plate (Millipore Corp., Bedford, MA, USA) and DNA sequencing data were produced by the ABI 3730xl DNA analyzer at Macrogen.…”
Section: Dna Extraction and Sequencing Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only slightly more than a third of the evaluated PAS-resistant strains had mutations in thyA, suggesting the existence of additional mechanisms of PAS resistance. Thr202Ala has been reported as the most common mutation associated with PAS resistance, although this mutation has also been identified in several PAS-susceptible isolates (Leung, Yip et al 2010).…”
Section: Paraaminosalicylic Acidmentioning
confidence: 99%